Overexpression of PLCG2 and TMEM38A inhibit tumor progression in clear cell renal cell carcinoma - Yiqiao Zhao; Liang Yang; Xiaojie Bai; Lu Du; Huan Lai; Yiyang Liu; Ping Chen; Michael E. DiSanto; Xinhua Zhang (Scientific Reports)
Abstract Clear cell renal cell carcinoma is a prevalent urological malignancy, imposing substantial burdens on both patients and society. In our study, we used bioinformatics methods to select four putative target genes associated with EMT and prognosis and developed a nomogram model which could accurately predicting 5-year patient survival rates. We further analyzed proteome and single-cell data and selected PLCG2 and TMEM38A for the following experiments. Overexpression models of PLCG2 and TMEM38A were generated in Caki-1 and 786-O cell lines using plasmids. The in vitro experiments demonstrated that both of them exerted pro-apoptotic effects on Caki-1 and 786-O cells, inducing G2/M phase arrest, inhibiting proliferation, and suppressing EMT. In summary, we identified potential tumor suppressor factors and stratified ccRCC patients into high-risk and low-risk groups based on these factors. Furthermore, we elucidated the impact of PLCG2 and TMEM38A in Caki-1 and 786-O cell lines, offering novel avenues for therapeutic target exploration.